Resources for Military Veterans in Higher Education: A Web-Based Content Analysis - Thomas R Cruise; Mitsunori Misawa (Adult Education Research Conference, 2019)
The purpose of this proposed web-based content analysis presentation is to explore the available resources for military veterans pursuing higher educational opportunities.
Keywords: veterans; higher education; resources; web-based content analysis